Nanomedicine of tyrosine kinase inhibitors - Smidova, Veronika; Michalek, Petr; Goliasova, Zita; Eckschlager, Tomas; Hodek, Petr; Adam, Vojtech; Heger, Zbynek (Theranostics, 2021)
Recent progress in nanomedicine and targeted therapy brings new breeze into the field of therapeutic applications of tyrosine kinase inhibitors (TKIs). These drugs are known for many side effects due to non-targeted mechanism of action that negatively impact quality of patients' lives or that are responsible for failure of the drugs in clinical trials. Some nanocarrier properties provide improvement of drug efficacy, reduce the incidence of adverse events, enhance drug bioavailability, helps to overcome the blood-brain barrier, increase drug stability or allow for specific delivery of TKIs to the diseased cells. Moreover, nanotechnology can bring new perspectives into combination therapy, which can be highly efficient in connection with TKIs. Lastly, nanotechnology in combination with TKIs can be utilized in the field of theranostics, i.e. for simultaneous therapeutic and diagnostic purposes. The review provides a comprehensive overview of advantages and future prospects of conjunction of nanotransporters with TKIs as a highly promising approach to anticancer therapy.
Keywords: nanomedicína; nanostruktury; Neoplasms; Protein Kinase Inhibitors; nádory; inhibitory proteinkinas; Nanomedicine; lékové transportní systémy; Drug Delivery Systems; Nanostructures; Humans; lidé